Synthesis of (+)-camptothecin - Chavan, Subhash P.; Venkatraman, M. S. (Arkivoc, 2005)
A synthesis of optically pure camptothecin was achieved in 4 steps from previously reported aldehyde employing Sharpless asymmetric dihydroxylation as the key step.
Keywords: Anticancer; camptothecin; sharpless asymmetric dihydroxylation

ORGN 511-Total synthesis of 7-chloro-10-methoxycamptothecin: an important synthon for commercially important derivatives of camptothecin - Sharma, Anil; Chavan, Subhash P.; Venkatraman, M. S. (Abstracts of Papers of the American Chemical Society, 2008)